Zwitterionic polymer electrolyte, preparation method and application
Patent Information
- Application Number
- CN202611409529.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]聚合物电解质室温离子电导率远低于液态电解质,这一差距根源在于聚合物链段紧凑堆积及锂离子与链段上极性基团之间的强配位作用,由此导致锂离子脱离配位束缚困难、迁移速率低下,严重制约了固态锂二次电池的循环性能与倍率性能
本发明提供了两性离子聚合物电解质的制备方法,所述聚合物电解质为三维瓶刷结构,带电基团均匀分布在该结构中。所述电解质具有优异的物理化学与电化学性能,包括高热稳定性、高离子电导率和宽电化学稳定窗口,可实现固态电池高性能稳定循环;
Smart Images

Figure CN123018122A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ionic polymer electrolyte technology, and in particular to an amphoteric ionic polymer electrolyte, its preparation method, and its application. Background Technology
[0002] Developing green and sustainable energy is a core strategy for addressing the energy crisis and environmental pollution, and breakthroughs in advanced energy storage technologies are crucial to its success. Lithium-ion batteries, as a core carrier in the new energy field, are driving the rapid development of industries such as new energy vehicles and smart electronics; however, the contradiction between their safety and energy density is becoming increasingly prominent. Against this backdrop, solid-state lithium-ion batteries based on polymer electrolytes, with their high safety, high energy density, and flexible design potential, are considered a breakthrough for next-generation energy storage technologies.
[0003] Polymer electrolytes exhibit significantly lower room-temperature ionic conductivity than liquid electrolytes. This difference stems from the compact packing of polymer segments and the strong coordination between lithium ions and polar groups on these segments. This results in difficulty for lithium ions to escape coordination constraints and a low migration rate, severely limiting the cycle performance and rate capability of solid-state lithium rechargeable batteries. To overcome these challenges, researchers have proposed various optimization strategies in recent years, including plasticizer modification and inorganic filler composites. These strategies aim to improve room-temperature ionic conductivity to some extent by expanding the amorphous region and enhancing segment movement. However, in-depth research indicates that lithium-ion transport efficiency depends not only on the local movement of polymer segments but also on the lithium-ion coordination environment. Zwitterionic polymers containing positively and negatively charged groups offer a novel perspective for reconstructing the lithium-ion coordination environment. Utilizing electrostatic interactions to regulate the coordination environment is a feasible approach to improve ion transport kinetics.
[0004] Therefore, it is necessary to design a zwitterionic polymer electrolyte to improve the ion transport dynamics inside the battery and enhance the overall performance of the battery. Summary of the Invention
[0005] The purpose of this invention is to provide an amphoteric polymer electrolyte, its preparation method, and its application. By using a competitive coordination method, it opens up a rapid transport channel for lithium ions in the electrolyte bulk phase, resulting in high ionic conductivity, high thermal stability, and a wide electrochemical stability window, which can achieve high-performance cycling of solid-state batteries.
[0006] To achieve the above objectives, the present invention provides an amphoteric polymer electrolyte comprising a lithium salt, an amphoteric polymer, an ether or ester polymer monomer, and an initiator; The molar ratio of lithium ions to repeating units of ether or ester polymer monomers in zwitterionic polymer electrolytes is (8~20):1; The molar ratio of ether or ester polymer monomers to zwitterionic polymers is 1:(0.1~1). The initiator content relative to ether or ester polymer monomers is 0.1-0.5 wt%; The zwitterionic polymer electrolyte has a bottle brush or three-dimensional network structure.
[0007] Preferably, the lithium salt concentration is 1~3M.
[0008] Preferably, the zwitterionic polymer includes 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, methacryloylethyl sulfobetaine, or 2-methacryloyloxyethyl phosphocholine.
[0009] Preferably, the ether or ester polymer monomers include polyethylene glycol diacrylate, methyl methacrylate, ethyl acrylate, maleic anhydride, acrylonitrile, N,N'-methylenebisacrylamide, or 2,2,2-trifluoroethyl acrylate.
[0010] A method for preparing an amphoteric polymer electrolyte, comprising the following specific steps: S1. In a near-anhydrous and oxygen-free environment, lithium salt, zwitterionic polymer, ether or ester polymer monomer, and initiator are added to the solvent in sequence and stirred until completely dissolved to obtain a precursor solution. S2. The precursor solution obtained in step 1 is transferred to a polytetrafluoroethylene plate, uniformly coated by a scraping method, cured by thermal initiation or photoinitiation polymerization, then allowed to stand, and then vacuum dried to obtain an amphoteric polymer electrolyte membrane.
[0011] Preferably, the thermally initiated polymerization method is used, with the initiator being a thermal initiator, and the curing process is completed by heat treatment at 60 degrees Celsius for 0.5 to 2 hours. Photoinitiated polymerization uses a photoinitiator as the initiator and is cured by irradiation in a UV curing chamber for 2-5 minutes.
[0012] Preferably, the drying temperature is 40~60℃ and the drying time is 12~24 hours.
[0013] Preferably, the solvent is acetonitrile, dichloromethane, or acetone.
[0014] Application of a zwitterionic polymer electrolyte and a method for preparing a zwitterionic polymer electrolyte in the preparation of lithium-ion batteries.
[0015] Therefore, the present invention employs the above-mentioned zwitterionic polymer electrolyte, its preparation method, and its application, and the technical effects are as follows: This invention provides a method for preparing a zwitterionic polymer electrolyte, wherein the polymer electrolyte has a three-dimensional bottle-brush structure with charged groups uniformly distributed within the structure. The electrolyte exhibits excellent physicochemical and electrochemical properties, including high thermal stability, high ionic conductivity, and a wide electrochemical stability window, enabling high-performance and stable cycling of solid-state batteries. This invention provides a method for enhancing the ion transport kinetics of polymer electrolytes. Negatively charged groups within the zwitterionic polymer compete with lithium ions for coordination, effectively weakening the strong coordination lock-in effect between lithium ions and polar groups; positively charged groups anchor lithium salt anions, effectively increasing the lithium ion transference number. This competitive coordination method enables the opening of rapid lithium ion transport channels in the bulk electrolyte phase. Attached Figure Description
[0016] Figure 1 These are scanning electron microscope images of the zwitterionic polymer electrolyte membranes prepared in Examples 1-4 of this invention; Figure 1 (a) is a planar view of the microstructure of the polymer electrolyte; Figure 1 (b) is a surface scan analysis plot of the corresponding micro-region with respect to the elements C, F, N and S; Figure 2 These are the linear sweep voltammetric curves of the zwitterionic polymer electrolytes prepared in Examples 1-4 of this invention; Figure 3 These are the thermogravimetric curves of the zwitterionic polymer electrolytes prepared in Examples 1-4 of this invention; Figure 4 These are the ionic conductivity-temperature curves and Arrhenius curves of the zwitterionic polymer electrolytes prepared in Examples 1-4 of this invention; Figure 4 (a) is the ionic conductivity-temperature curve of the zwitterionic polymer electrolyte; Figure 4 (b) shows the Arrhenius curve and the corresponding ion migration barrier value; Figure 5 These are the electrochemical cycling data obtained from the zwitterionic polymer electrolyte matched coin cell prepared in Example 2 of this invention. Detailed Implementation
[0017] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0018] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0019] This invention provides an amphoteric polymer electrolyte, its preparation method, and its application. The amphoteric polymer electrolyte comprises a lithium salt, an ether or ester polymer monomer, an amphoteric polymer, and an initiator. A crosslinking copolymerization reaction between the amphoteric polymer and the ether / ester polymer monomer is achieved through free radical-initiated polymerization, constructing a competitive coordination structure for lithium ions at the molecular scale. Specifically, the reaction mechanism involves the initiator decomposing to generate primary free radicals, which attack the C=C double bonds in the ether / ester monomer and the amphoteric polymer, causing the π bonds to break and generating carbon free radical active centers. These carbon free radicals then continuously attack other double bonds, initiating chain growth. The successive opening and connection of double bonds form the copolymer backbone, and chemical crosslinking bonds are formed between polymer chains, constructing a three-dimensional bottle brush network. This reaction bonds the anionic and cationic groups in the amphoteric ion to the backbone, synergistically with the polar groups on the backbone, constructing a competitive coordination structure for lithium ions at the molecular scale, promoting lithium salt dissociation and rapid transport, and increasing the migration number and ionic conductivity.
[0020] The lithium salt bis(trifluoromethanesulfonyl)imide used in the following examples can be replaced with other commonly available lithium salts, including but not limited to lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, and lithium trifluoromethanesulfonate.
[0021] The initiator azobisisobutyronitrile used in the following examples can be replaced with other commercially available initiators. Photoinitiators include, but are not limited to, 2-hydroxy-2-methyl-1-phenylpropanone, Irgacure 2959, benzoin ether, camphorquinone, and benzophenone / thioxanthone derivatives. Thermal initiators include, but are not limited to, benzoyl peroxide, azobisisobutyramidine hydrochloride, and VA-044.
[0022] (1) Scanning electron microscope test: Scanning electron microscope, model S-4800; (2) Linear scanning voltammetry test: Electrochemical workstation, model: CHI660e, Shanghai Chenhua Instrument Co., Ltd. The specific method is as follows: Assemble a stainless steel | polyether electrolyte | lithium-ion battery system and set the scan rate to 0.1 mV / s; (3) Thermogravimetric analysis: Thermogravimetric analyzer, model: Netzsch STA 449 F3 / F5; (4) Full battery cycle test: LAND CT2001A tester.
[0023] Experimental Example 1 A method for preparing an amphoteric polymer electrolyte includes the following steps: S1. In a glove box filled with a protective gas of argon with a purity of ≥99% and a moisture content of ≤0.1ppm, 1g of polyethylene glycol diacrylate and 0.186g of 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate were added to 0.3g of acetonitrile solvent and stirred for 12 hours. Then, 0.345g of lithium bis(trifluoromethanesulfonyl)imide was added and stirred until completely dissolved. Finally, 0.003g of azobisisobutyronitrile was added to the solution and stirred for 3 hours to obtain the precursor solution.
[0024] S2. Transfer the precursor solution to a polytetrafluoroethylene plate and coat it evenly using a blade coating method. Heat treat it at 60 degrees Celsius for 1 hour to cure it, let it stand for 12 hours, and then vacuum dry it at 50 degrees Celsius for 24 hours to remove residual organic solvents, thus obtaining an amphoteric polymer electrolyte membrane.
[0025] S3. The prepared zwitterionic polymer electrolyte membrane is matched with positive electrode materials (including lithium iron phosphate, lithium cobalt oxide and nickel cobalt manganese ternary materials) and negative electrode lithium metal materials to assemble coin cells, thereby obtaining a lithium battery based on zwitterionic polymer.
[0026] The zwitterionic polymer electrolyte prepared in this example was tested, and the results are as follows: (1) Scanning electron microscope image: The scanning electron microscope image of the zwitterionic polymer electrolyte membrane prepared in this embodiment is shown below. Figure 1 As shown.
[0027] (2) Linear sweep voltammetry: The linear sweep voltammetry curve of the zwitterionic polymer electrolyte prepared in this embodiment is shown in Figure 1. Figure 2 As shown.
[0028] (3) Thermogravimetric analysis: The thermogravimetric curve of the zwitterionic polymer electrolyte prepared in this embodiment is as follows: Figure 3 As shown.
[0029] (4) Ionic conductivity test: The ionic conductivity-temperature curve and Arrhenius curve of the zwitterionic polymer electrolyte prepared in this embodiment are shown in the figure. Figure 4 As shown.
[0030] Example 2 A method for preparing an amphoteric polymer electrolyte includes the following steps: S1. In a glove box filled with a protective gas of argon with a purity of ≥99% and a moisture content of ≤0.1ppm, 1g of polyethylene glycol diacrylate and 0.195g of methacryloyl ethyl sulfobetaine were added to 0.3g of acetonitrile solvent and stirred for 12 hours. Then, 0.345g of lithium bis(trifluoromethanesulfonyl)imide was added and stirred until completely dissolved. Finally, 0.003g of azobisisobutyronitrile was added to the solution and stirred for 3 hours to obtain the precursor solution.
[0031] S2. Transfer the precursor solution to a polytetrafluoroethylene plate and coat it evenly using a blade coating method. Heat treat it at 60 degrees Celsius for 1 hour to cure it, let it stand for 12 hours, and then vacuum dry it at 50 degrees Celsius for 24 hours to remove residual organic solvents, thus obtaining an amphoteric polymer electrolyte membrane.
[0032] S3. The prepared zwitterionic polymer electrolyte membrane is matched with positive electrode materials (including lithium iron phosphate, lithium cobalt oxide and nickel cobalt manganese ternary materials) and negative electrode lithium metal materials to assemble coin cells, thereby obtaining a lithium battery based on zwitterionic polymer.
[0033] The zwitterionic polymer electrolyte prepared in this example was tested, and the results are as follows: (1) Scanning electron microscope image: The scanning electron microscope image of the zwitterionic polymer electrolyte membrane prepared in this embodiment is shown below. Figure 1 As shown.
[0034] (2) Linear sweep voltammetry: The linear sweep voltammetry curve of the zwitterionic polymer electrolyte prepared in this embodiment is shown in Figure 1. Figure 2 As shown.
[0035] (3) Thermogravimetric analysis: The thermogravimetric curve of the zwitterionic polymer electrolyte prepared in this embodiment is as follows: Figure 3 As shown.
[0036] (4) Ionic conductivity test: The ionic conductivity-temperature curve and Arrhenius curve of the zwitterionic polymer electrolyte prepared in this embodiment are shown in the figure. Figure 4 As shown.
[0037] (5) Full-cell cycle data: The electrochemical cycle data of the zwitterionic polymer electrolyte-matched coin cell prepared in this embodiment are as follows: Figure 5 As shown.
[0038] Example 3 A method for preparing an amphoteric polymer electrolyte includes the following steps: S1. In a glove box filled with a protective gas of argon with a purity of ≥99% and a moisture content of ≤0.1ppm, 1g of polyethylene glycol diacrylate and 0.208g of 2-methacryloyloxyethyl phosphocholine were added to 0.3g of acetonitrile solvent and stirred for 12 hours. Then, 0.345g of lithium bis(trifluoromethanesulfonyl)imide was added and stirred until completely dissolved. Finally, 0.003g of azobisisobutyronitrile was added to the solution and stirred for 3 hours to obtain the precursor solution.
[0039] S2. Transfer the precursor solution to a polytetrafluoroethylene plate and coat it evenly using a blade coating method. Heat treat it at 60 degrees Celsius for 1 hour to cure it, let it stand for 12 hours, and then vacuum dry it at 50 degrees Celsius for 24 hours to remove residual organic solvents, thus obtaining an amphoteric polymer electrolyte membrane.
[0040] S3. The prepared zwitterionic polymer electrolyte membrane is matched with positive electrode materials (including lithium iron phosphate, lithium cobalt oxide and nickel cobalt manganese ternary materials) and negative electrode lithium metal materials to assemble coin cells, thereby obtaining a lithium battery based on zwitterionic polymer.
[0041] The zwitterionic polymer electrolyte prepared in this example was tested, and the results are as follows: (1) Scanning electron microscope image: The scanning electron microscope image of the zwitterionic polymer electrolyte membrane prepared in this embodiment is shown below. Figure 1 As shown.
[0042] (2) Thermogravimetric analysis: The thermogravimetric curve of the zwitterionic polymer electrolyte prepared in this embodiment is as follows: Figure 3 As shown.
[0043] (3) Ionic conductivity test: The ionic conductivity-temperature curve and Arrhenius curve of the zwitterionic polymer electrolyte prepared in this embodiment are shown in the figure. Figure 4 As shown.
[0044] Example 4 A method for preparing an amphoteric polymer electrolyte includes the following steps: S1. In a glove box filled with a protective gas of argon with a purity of ≥99% and a moisture content of ≤0.1ppm, 1g of methyl methacrylate and 0.195g of methacryloyl ethyl sulfobetaine were added to 0.3g of acetonitrile solvent and stirred for 12 hours. Then, 0.345g of lithium bis(trifluoromethanesulfonyl)imide was added and stirred until completely dissolved. Finally, 0.003g of azobisisobutyronitrile was added to the solution and stirred for 3 hours to obtain the precursor solution.
[0045] S2. Transfer the precursor solution to a polytetrafluoroethylene plate and coat it evenly using a blade coating method. Heat treat it at 60 degrees Celsius for 1 hour to cure it, let it stand for 12 hours, and then vacuum dry it at 50 degrees Celsius for 24 hours to remove residual organic solvents, thus obtaining an amphoteric polymer electrolyte membrane.
[0046] S3. The prepared zwitterionic polymer electrolyte membrane is matched with positive electrode materials (including lithium iron phosphate, lithium cobalt oxide and nickel cobalt manganese ternary materials) and negative electrode lithium metal materials to assemble coin cells, thereby obtaining a lithium battery based on zwitterionic polymer.
[0047] The zwitterionic polymer electrolyte prepared in this example was tested, and the results are as follows: (1) Thermogravimetric test: The thermogravimetric curve of the zwitterionic polymer electrolyte prepared in this embodiment is as follows: Figure 3 As shown.
[0048] (2) Ionic conductivity test: The ionic conductivity-temperature curve and Arrhenius curve of the zwitterionic polymer electrolyte prepared in this embodiment are shown in the figure. Figure 4 As shown.
[0049] Example 5 A method for preparing an amphoteric polymer electrolyte includes the following steps: S1. In a glove box filled with a protective gas of argon with a purity of ≥99% and a moisture content of ≤0.1ppm, 1g of polyethylene glycol diacrylate and 0.195g of methacryloyl ethyl sulfobetaine were added to 0.3g of acetonitrile solvent and stirred for 12 hours. Then, 0.345g of lithium bis(trifluoromethanesulfonyl)imide was added and stirred until completely dissolved. Finally, 0.003g of 2-hydroxy-2-methyl-1-phenylpropanone was added to the solution and stirred for 3 hours to obtain the precursor solution.
[0050] S2. Transfer the precursor solution to a polytetrafluoroethylene plate and coat it evenly using a blade coating method. Cure it by irradiation in a UV curing oven for 2-5 minutes, let it stand for 12 hours, and then vacuum dry it at 50 degrees Celsius for 24 hours to remove residual organic solvents, obtaining an amphoteric polymer electrolyte membrane.
[0051] S3. The prepared zwitterionic polymer electrolyte membrane is matched with positive electrode materials (including lithium iron phosphate, lithium cobalt oxide and nickel cobalt manganese ternary materials) and negative electrode lithium metal materials to assemble coin cells, thereby obtaining a lithium battery based on zwitterionic polymer.
[0052] The zwitterionic polymer electrolyte prepared in this example was tested, and the results are as follows: Scanning electron microscope (SEM) images: The SEM images of the zwitterionic polymer electrolyte membrane prepared in this embodiment are shown below. Figure 1 As shown.
[0053] Therefore, the present invention employs the above-mentioned zwitterionic polymer electrolyte, preparation method and application, and realizes the opening of a fast transport channel for lithium ions in the electrolyte bulk phase through competitive coordination method, which has high ionic conductivity, high thermal stability and wide electrochemical stability window, and can achieve high-performance cycling of solid-state batteries.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A zwitterionic polymer electrolyte, characterized in that, Including lithium salts, zwitterionic polymers, ether or ester polymer monomers, and initiators; The molar ratio of lithium ions to repeating units of ether or ester polymer monomers in zwitterionic polymer electrolytes is (8~20):1; The molar ratio of ether or ester polymer monomers to zwitterionic polymers is 1:(0.1~1). The initiator content relative to ether or ester polymer monomers is 0.1-0.5 wt%; The zwitterionic polymer electrolyte has a bottle brush or three-dimensional network structure.
2. The zwitterionic polymer electrolyte according to claim 1, characterized in that, The lithium salt concentration is 1~3M.
3. The zwitterionic polymer electrolyte according to claim 1, characterized in that, Amphoteric polymers include 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, methacryloylethyl sulfobetaine, or 2-methacryloyloxyethyl phosphocholine.
4. The method for preparing an amphoteric polymer electrolyte according to claim 1, characterized in that, Ether or ester polymer monomers include polyethylene glycol diacrylate, methyl methacrylate, ethyl acrylate, maleic anhydride, acrylonitrile, N,N'-methylenebisacrylamide, or 2,2,2-trifluoroethyl acrylate.
5. The method for preparing an amphoteric polymer electrolyte according to claim 1, characterized in that, The specific steps are as follows: S1. In a near-anhydrous and oxygen-free environment, lithium salt, zwitterionic polymer, ether or ester polymer monomer, and initiator are added to the solvent in sequence and stirred until completely dissolved to obtain a precursor solution. S2. The precursor solution obtained in step 1 is transferred to a polytetrafluoroethylene plate, uniformly coated by a scraping method, cured by thermal initiation or photoinitiation polymerization, then allowed to stand, and then vacuum dried to obtain an amphoteric polymer electrolyte membrane.
6. The method for preparing an amphoteric polymer electrolyte according to claim 5, characterized in that, Thermally initiated polymerization uses a thermal initiator and involves heat treatment at 60 degrees Celsius for 0.5 to 2 hours to complete the curing process. Photoinitiated polymerization uses a photoinitiator as the initiator and is cured by irradiation in a UV curing chamber for 2-5 minutes.
7. The method for preparing an amphoteric polymer electrolyte according to claim 5, characterized in that, The drying temperature is 40~60℃, and the drying time is 12~24 hours.
8. The method for preparing an amphoteric polymer electrolyte according to claim 5, characterized in that, The solvent is acetonitrile, dichloromethane, or acetone.
9. The application of the zwitterionic polymer electrolyte according to claim 1 and the preparation method of the zwitterionic polymer electrolyte according to claim 5 in the preparation of lithium-ion batteries.
